2022
DOI: 10.1155/2022/1254824
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Biochemical Parameters between Mouse Model and Human after Paraquat Poisoning

Abstract: Background. This study was designed to investigate differences in biochemical parameters between mouse and humans after paraquat (PQ) poisoning and develop a suitable animal model for studying organ damage after PQ poisoning. The prognostic factors of PQ-poisoned patients were further analyzed. Methods. Thirty C57BL/6J mice were randomly divided into five groups (control, sham, and 3 PQ doses), and the mouse model was established by intragastric administration of PQ. Physiological indexes such as the body weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…Following PQ administration, there was a notable increase in blood potassium levels alongside a significant decrease in hematocrit levels. Consistent with our findings, Yu et al noted that the elevation in serum potassium after acute PQ exposure could be attributed to renal failure and impaired potassium excretion 26 . Moreover, Okolonkwo et al showed that the substantial decline in blood hemoglobin levels might be associated with red blood cell destruction 27 .…”
Section: Discussionsupporting
confidence: 92%
“…Following PQ administration, there was a notable increase in blood potassium levels alongside a significant decrease in hematocrit levels. Consistent with our findings, Yu et al noted that the elevation in serum potassium after acute PQ exposure could be attributed to renal failure and impaired potassium excretion 26 . Moreover, Okolonkwo et al showed that the substantial decline in blood hemoglobin levels might be associated with red blood cell destruction 27 .…”
Section: Discussionsupporting
confidence: 92%
“…The study also included 29 human patients with diquat poisoning, who showed decreased levels of potassium and chloride, which led to death. The dead patients had higher levels of alanine aminotransferase, aspartate aminotransferase, blood urea nitrogen, and amylase, and high neutrophil-to-lymphocyte ratio [ 37 ]. These studies suggest that a combination of certain factors could accurately predict the outcomes of patient in diquat poisoning.…”
Section: Discussionmentioning
confidence: 99%